First Record of the Flower Bud Fly Dasiops inedulis Steyskal, 1980 (Diptera: Lonchaeidae) in Northeastern Brazil - Barros, Gabriel R.; Gisloti, Laura J.; Silveira, Francisca L. da C.; Calvet, Érica C. (Entomological Communications, 2025)
Passion fruit cultivation in Northeastern Brazil stands out in terms of both production and productivity when compared to other regions of the country. However, the incidence of arthropod pests during crop management poses a significant challenge. Among the various pest species, the presence of dipterans commonly known as flower bud flies, belonging to the genera Dasiops Rondani (1856) and Neosilba McAlpine (1962) (Diptera: Lonchaeidae), is particularly noteworthy. Both genera have been reported on plants in the Passifloraceae, with species from the genus Dasiops being primarily associated with the abscission of reproductive structures, which represents the main limiting factor in achieving high yields. In this context, the aim of this study was to identify the main species of flower bud fly present in passion fruit plantations in producing regions of the state of Ceará. To this end, five collections of infested flower buds were carried out. In Brazil, the species Dasiops inedulis Steyskal, 1980 has already been recorded in six states; this study represents the first record of the species in the state of Ceará.